(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Enteric-borne diarrheal illnesses are significant causes of human morbidity and mortality. Over 2 million diarrhea-related fatalities happen annually, especially among kids under the age of five. During the period extended from February 2019 to June 2019, A total of 196 stool locally specimens from diarrheal patients samples were collected from AL-Anbar city of AL-Ramadi hospital and AL-Fallujah hospital out of 196 samples diagnosis by biochemical test , morphology and selective chromogenic medium, found 80 samples of E. coli . The aim of the study detection of VT1 and VT2 genes in Escherichia coli isolated from Diarrhea patients by using PCR Sequencing. The result showed when diagnosis by PCR for Sanger Sequencing technique for VT1 and VT2 genes E. coli O157:H7,and E. coli O25b:H4 were positive for VT1gene ,and Escherichia coli O25b:H4 ,and Escherichia coli O18:H1 positive for VT2gene.